THE RELATIONSHIP OF PERSONALITY TYPE AND SELF-EFFICACY WITH MENTAL HEALTH AMONG ADOLESCENTS - Fakhrun Nisa' Fiddaroini; Nur Musayyidah; Eliza Zihni Zatihulwani (LPPM STIKES HUSADA JOMBANG, 2026)
Background: Adolescents face various challenges that increase their vulnerability to mental health problems. Adaptive coping strategies and self-efficacy are important factors in maintaining mental well-being, while personality type influences adolescents’ ability to adapt. Objectives: This study aimed to determine the relationship of personality type and self-efficacy with mental health among adolescents at MA Mazroatul Ulum Paciran Lamongan. Methods: This study used an analytic correlational approach with a cross-sectional design. The population consisted of 89 twelfth-grade students, with 73 respondents selected using simple random sampling. Independent variables were personality type and self-efficacy, while mental health was the dependent variable. Instruments included the Jung Type Indicator Questionnaire, the General Self-Efficacy Scale, and the Mental Health Continuum–Short Form. Data were analyzed using the Chi-square test and Spearman’s rank correlation test with a significance level of p < 0.05. Results: Most respondents had an extroverted personality type, high self-efficacy (68.5%), and high mental health levels (69.9%). The Chi-square test showed a significant relationship between personality type and mental health (p < 0.001, OR = 41.4). The Spearman’s rank correlation test also indicated a significant and very strong relationship between self-efficacy and mental health (p < 0.001, r = 0.758). Conclusion: Introverted adolescents were more likely to experience poor mental health than extroverted adolescents. Higher self-efficacy was associated with better mental health. Personality type and self-efficacy significantly influence adolescents’ mental health. Nurses play an important role in providing mental health education for adolescents.